Evaluation sensitometric properties of radiographic films at different processing solutions - Mojiri, Maryam; Ghazi khanloo sani, Karim; Moghim Beigi, Abbas (Archives of Advances in Biosciences, 2011)
The aim of this study is to compare the sensitometric properties of commonly used radiographic films processed with chemical solutions in different workload hospitals. The effect of different processing conditions on induced densities on radiologic films was investigated. Two accessible double emulsions Fuji and Kodak films were exposed with 11-step wedge and processed with Champion and CPAC processing solutions. The mentioned films provided in both workloads centers, high and low. Our findings displays that the speed and contrast of Kodak film-screen in both work load (high and low) is higher than Fuji film-screen for both processing solutions. However there was significant differences (p=0.000 and 0.028) in films contrast for both workloads when CPAC solution had been used. The results showed base plus fog density for Kodak film was lower than Fuji. Generally Champion processing solution caused more speed and contrast for investigated films in different conditions and there was significant difference(p=0.01) in 95% confidence level between two used processing solutions. Low base plus fog density for Kodak films provide more visibility and accuracy and higher contrast results in using lower exposure factors to obtain better quality in resulting radiographs. In this study we found an economic advantages since Champion solution and Kodak film are used while it makes lower patient dose. Thus, in a radiologic facility any change in film processor/processing cycle or chemistry should be carefully investigated before radiological procedures of patients are acquired.